2007
DOI: 10.1128/mcb.02289-05
|View full text |Cite
|
Sign up to set email alerts
|

The 3′ Untranslated Region Complex Involved in Stabilization of Human α-globin mRNA Assembles in the Nucleus and Serves an Independent Role as a Splice Enhancer

Abstract: Posttranscriptional controls, mediated primarily by RNA-protein complexes, have the potential to alter multiple steps in RNA processing and function. Human ␣-globin mRNA is bound at a C-rich motif in the 3 untranslated region (3UTR) by the KH domain protein ␣-globin poly(C)-binding protein (␣CP). This "␣-complex" is essential to cytoplasmic stability of ␣-globin mRNA in erythroid cells. Here we report that the 3UTR ␣-complex also serves an independent nuclear role as a splice enhancer. Consistent with this rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 53 publications
5
45
0
Order By: Relevance
“…The PR was replaced with an equal sized ''neutral'' sequence derived from the coding region of the ha-globin mRNA . This substitution is known to abolish aCP binding in mammalian erythroid cells, resulting in defects in stability , splicing (Ji et al 2007), and 39end formation (X Ji and SA Liebhaber, in prep.). The ha Neut 39 UTR ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PR was replaced with an equal sized ''neutral'' sequence derived from the coding region of the ha-globin mRNA . This substitution is known to abolish aCP binding in mammalian erythroid cells, resulting in defects in stability , splicing (Ji et al 2007), and 39end formation (X Ji and SA Liebhaber, in prep.). The ha Neut 39 UTR ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While of potential interest, these studies failed to demonstrate whether XaCP2 did, in fact, bind in vivo to the pp2Ac mRNA target and/or interact with the cytoplasmic polyadenylation machinery. The possibility that aCP2 plays a direct role in targeting cytoplasmic polyadenylation is of particular interest because this same protein, also known as heterogeneous nuclear ribonucleoprotein E2 (hnRNP E2)/ poly(rC) binding protein 2 (PCBP2), has been implicated in multiple post-transcriptional control pathways in mammalian cells, including splicing (Ji et al 2007), 39 end formation (X Ji and SA Liebhaber, in prep. ), translational control , and stabilization of long-lived mRNAs via poly (A) tail maintenance .…”
Section: Introductionmentioning
confidence: 99%
“…It was recently discovered that αCPs are loaded onto α-globin transcripts in the nucleus and in addition to the 3'UTR, also bind a Crich region in intron 1. 37 In HeLa cells selectively depleted of αCP, splicing efficiency of a truncated α-globin construct (comprising exon 1, intron 1 and exon 2) was increased approximately four-fold from 15% to 58%. Thus, it appears that nuclear αCP binding to intron 1 represses splicing of the α-globin transcript.…”
Section: T O R T I F O U N D a T I O Nmentioning
confidence: 97%
“…Conversely, nuclear binding of αCP to the 3'UTR appears to enhance splicing of the α-globin pre-mRNA. 37 Experiments were conducted in HeLa and MEL cells comparing WT α-globin and a mutated transcript with a modified 3'UTR which does not bind αCP (α∆PR). In both cell types, it was found that WT transcripts were spliced with higher efficiency than mutated α∆PR transcripts.…”
Section: T O R T I F O U N D a T I O Nmentioning
confidence: 99%
See 1 more Smart Citation